Dynamic, multi-objective optimal design and operation of water-energy systems for small, off-grid islands. (15th September 2019) - Giudici, Federico; Castelletti, Andrea; Garofalo, Elisabetta; Giuliani, Matteo; Maier, Holger R.
Highlights: A dynamic, multi-objective approach to optimize off-grid water-energy systems is proposed. Interdependency between system design and operations is considered. The nexus between water and energy systems is modelled dynamically. The approach outperforms the state-of-the-art non-dynamic, least cost approach. The optimal solutions identified limit investment costs and environmental impacts. Abstract: Small Mediterranean islands are remote, off-grid communities characterized by carbon intensive electricity systems coupled with high energy consuming desalination technologies to produce potable water. The aim of this study is to propose a novel dynamic, multi-objective optimization approach for improving the sustainability of small islands through the introduction of renewable energy sources. The main contributions of our approach include: (i) dynamic modelling of desalination plant operations, (ii) joint optimization of system design and operations, (iii) multi-objective optimization to explore trade-offs between potentially conflicting objectives. We test our approach on the real case study of the Italian Ustica island by means of a comparative analysis with a traditional non-dynamic, least cost optimization approach. Numerical results show the effectiveness of our approach in identifying optimal system configurations, which outperform the traditional design with respect to different sustainability indicators, limiting the structural interventions, the investment costs and the environmental impacts. In particular, the optimal dynamic solutions able to satisfy the whole water demand allow high levels of penetration of renewable energy sources (up to more than 40%) to be reached, reducing the net present cost by about 2–3 M€ and the CO2 emissions by more than 200 tons/y.